Fatigue assessment and its predictors in pediatric patients with chronic kidney disease stages III to V - Yasmin Ramadan; Nehal Elkoofy; Samar Sabry; Ghada Mansour; Noha El-Anwar (SpringerOpen, 2023)
Abstract Background Chronic fatigue is an intense subjective feeling of mental or physical exhaustion. It influences patients' daily functioning and quality of life, delays recovery, and increases mortality, especially in chronic kidney disease (CKD) patients. The aim of this study is to assess and determine predictors of chronic fatigue in children with ESRD, dialysis, and pre-dialysis stages that can affect the patients' quality of life (QOL). Methods We conducted a cross-sectional study on 114 patients diagnosed with CKD stages III to V, following at the nephrology outpatient clinic and hemodialysis (HD) unit of Cairo University Children's Hospital during the period September 2020 till April 2021. Demographic and laboratory data of patients were gathered, and dialytic analysis in the form of frequency, duration of dialysis sessions, and adequacy of hemodialysis was calculated. The fatigue severity score (FSS) questionnaire was used to assess fatigue's effects on daily functions, querying its relationship to motivation, physical activity, work, family, and social life. Results The mean age in the current study was (8.8 ± 1.8) years, with 62% being males. The median FSS score was 5.8, with a higher FSS score in stage V CKD patients. High e-GFR, serum sodium, folic acid, and L-carnitine supplementation all reduced the intensity of fatigue, while prolonged HD duration, acidosis, hypertension, and non-compliance to vitamin D replacement increased tiredness severity. Conclusion Routine fatigue assessment and measures to reduce it is a fundamental issue in pediatric CKD patients for better QOL.